(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the training of personnel in the field of ecology, life safety and technosphere safety on the basis of the Kyrgyz-Russian Slavic University named after I. B. Yeltsin, as well as areas of cooperation with the Irkutsk National Research Technical University.